June bloom in Maratea - Parcy, François; Lohmann, Jan U. (Development, 2011)
The International Workshop on Molecular Mechanisms Controlling Flower Development took place in the secluded southern Italian village of Maratea in June 2011. This meeting, which takes place biennially, gathers researchers in the fields of flowering time and flower and fruit development from both Europe and overseas to enjoy the sun, the sea and, most importantly, the science. As we summarise here, the results presented at this workshop underlined how mechanistic studies of both model and diverse species are deepening our understanding of the cellular processes involved in flowering.